IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA DI KELAS IX-G SMPN 1 SIDIKALANG - Dormian Samosir (Universitas Negeri Medan, 2018)
Abstract: Implementation Of Cooperative Learning Model Type Think Pair Share (TPS) To Increase Student Learning Results Students In Class IX-G SMPN 1 Sidikalang. The objective of this research is to improve learning result and student learning activity by using cooperative learning model Think Pairs Share (TPS) in class IX-G SMPN 1 Sidikalang. The subject of this study was taken in class IX-G SMPN 1 Sidikalang with the number of students 27 people. Based on the research, the conclusion is as follows: 1) The increase of student learning outcomes by applying the model of thinking pair share that is the individual completeness of 11 students for cycle I and 24 students for Cycle II with the completeness of class in Cycle I and Cycle II is 40% and 88%; 2) The increase of student learning activity after applying think pair share model, while the student activity data according to observer observation in cycle I are: writing / reading (44,1%), doing LKS (24,7%), asking fellow friend 14.1%), asked the teacher (10.0%), and which is not relevant to the KBM (7.1%).Keywords: Model of cooperative learning type of TPS, Student Learning Outcomes, Student Learning Activities.Abstrak : Implementasi Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Hasil Belajar IPS Siswa di Kelas IX-G SMPN 1 Sidikalang. Penelitian bertujuan untuk meningkatkan hasil belajar dan aktivitas belajar siswa dengan menggunakan model pembelajaran kooperatif tipe Think Pairs Share (TPS) di kelas IX-G SMPN 1 Sidikalang. Subjek penelitian ini diambil di kelas IX-G SMPN 1 Sidikalang dengan jumlah siswa 27 orang. Berdasarkan penelitian yang dilakukan didapat kesimpulan sebagai berikut: 1) Adanya peningkatan hasil belajar siswa dengan menerapkan model pembelajaran think pair share yakni ketuntasan individu sebanyak 11 orang siswa untuk siklus I dan 24 orang siswa untuk Siklus II dengan ketuntasan kelas pada Siklus I dan Siklus II adalah 40% dan 88%; 2) Adanya peningkatan aktivitas belajar siswa setelah menerapkan model think pair share, adapun data aktivitas siswa menurut pengamatan pengamat pada siklus I antara lain: menulis/membaca (44,1%), mengerjakan LKS (24,7% ), bertanya sesama teman (14,1%), bertanya kepada guru (10,0%), dan yang tidak relevan dengan KBM (7,1%).Kata Kunci : Model Pembelajaran kooperatif tipe TPS, Hasil Belajar Siswa, Aktivitas Belajar Siswa.